ANALISIS EFEKTIVITAS INKLUSI KEUANGAN DI BMT SYARIAH RIYAL - Khatimah, Husnul (Fakultas Ekonomi Universitas Islam 45, 2016)
This study aims to explain the policy implementation strategy of BMT in improving access to financial facilities for small enterprises (SMEs) in Bekasi. Measuring the effectiveness of the strategy of inclusion and financial literacy policy that has been applied to small enterprises (SMEs) in Bekasi. Finding advanced strategies that can be applied to optimize the function of BMT in promoting inclusion and financial literacy, especially in Bekasi. The method used is a qualitative method approach to field exploration, in-depth interview. The results of the interview data obtained mapped by categories, namely internal and external factors then analyzed using SWOT matrix and IE. Subsequently made an evaluation of the implementation of existing strategies and formulating strategies that will come in order to improve public financial inclusion. The results showed that the financial inclusion strategy applied BMT Syariah Riyal (BSR) is quite helpful in increasing financial inclusion, especially in the city of Bekasi, even BSR has developed a marketing area as well as services to the Bekasi area. In an effort to increase financial inclusion in society, BSR to work with various elements, among others, people in target areas: the RT, RW, taklim, schools, the local parliament constituency. In the medium term BSR develop proactive strategies and strengthen human resources, networks, information systems and capital in order to increase the reach of its services to the public.